Fundos de investimento: uma análise da dinâmica entre tamanho, captação e rentabilidade - Matta, Rafaela Palma da (2010)
This paper aims to evaluate how a fund's return is related to its size, total assets under management of the fund’s manager institution among other factors. For the proposed tests, we used the panel data regression model. The analysis covers all the available information of the last five years (May 2005 to April 2010) for two funds categories: Multimarket and Equities. Another investigated poin t is the factors that may explain the fund’s subscriptions. In this case, the fund’s return and its Sharpe Ratio over the last six months were used as possible independent variables.